The effect of cancer warning statements on alcohol consumption intentions. - Pettigrew, Simone; Jongenelis, Michelle; Glance, D.; Chikritzhs, Tanya; Pratt, I.; Slevin, Terry; Liang, Wenbin; Wakefield, M. (2016)
In response to increasing calls to introduce warning labels on alcoholic beverages, this study investigated the potential effectiveness of alcohol warning statements designed to increase awareness of the alcohol-cancer link. A national online survey was administered to a diverse sample of Australian adult drinkers (n = 1,680). Along with attitudinal, intentions and demographic items, the survey included an online simulation that exposed respondents to one of six cancer warning statements delivered across a range of situational contexts. Half of the statements made general reference to cancer and half mentioned specific forms of cancer. Respondents reported on the believability, convincingness and personal relevance of the warning statements. Pre- and post-exposure data were captured relating to respondents' alcohol consumption intentions. Of the six statements tested, Alcohol increases your risk of bowel cancer produced the highest scores across all outcome measures. All statements produced favorable changes in alcohol consumption intentions, including among high-risk drinkers. There is thus the potential for these and similar statements to be used as a suite of rotating warning messages located on alcoholic beverage labels and applied in various public education contexts.